The simplicity principle : six steps towards clarity in a complex world - Hobsbawm, Julia (Kogan Page, 2020)
"Modern life is complicated, much more so than it used to be. Acclaimed author and social entrepreneur, Julia Hobsbawm, shows you a simpler way. The Simplicity Principle challenges the assumption that all things that are complex have to stay that way. It helps keep things as lean, simple and focused as possible. Smartphone users experience concentration interruptions every 12 minutes of the day, there are over 250 billion emails sent every 24 hours and by 2021 the internet will have created more than 3.3 zettabytes of data. Yet complexity doesn't have to dominate, complicate or clutter our lives. Based on a hexagonal model, this book shows you that it's easy to streamline and simplify both your professional and personal lives with lessons based on the natural world. For anyone who feels that life can be too much, The Simplicity Principle will help you break free of the endless choices and complexities that we face in the world today. It's time to gain control of your focus and productivity, and most importantly, KEEP IT SIMPLE"--